Newfoundland and Labrador Centre for Health Information - Network Update - Steve O'Reilly (ElectronicHealthcare, 2001)
The Newfoundland and Labrador Centre for Health Information was established to make the province's Health System Information Task Force's vision of a quality person-centred health information system a reality. Since 1996, the centre has been working with partners to develop a comprehensive Health Information Network. The centre has obtained government support to build the unique personal identifier/client registry, and is presently finalizing a proposal to government to fund a project for the Newfoundland and Labrador Pharmacy Network. Work also continues at Newfoundland and Labrador Centre for Health Information towards the development and dissemination of quality health information.